Case 3695: Dimetrodon Cope, 1878 (Synapsida, Sphenacodontidae): proposed conservation by reversal of precedence with Bathygnathus Leidy, 1853 - Brink, K S (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the widely used generic name Dimetrodon Cope, 1878 (Sphenacodontoidea, Sphenacodontidae). The name Dimetrodon is threatened by its senior subjective synonym Bathygnathus Leidy, 1853. The name Dimetrodon has become widely accepted and is in prevailing usage. It is proposed that Dimetrodon be given precedence over Bathygnathus whenever these names are considered to be synonyms.
Keywords: Nomenclature; taxonomy; Synapsida; SPHENACODONTOIDEA; SPHENACODONTIDAE; Bathygnathus; Bathygnathus borealis; Dimetrodon; Permian; Canada; U.S.A.